Violence and African Philosophy: Beyond Reaction and Mimicry - Sanni, John Sodiq (African studies (Johannesburg), 2025)
The history of African philosophy often begins with the quest for legitimacy, by which I mean the desire for it to be recognised, accepted and considered as critical thinking in the real sense of the word. This starting point, on the part of many African philosophy scholars, was due to the historical epistemic violence that Africans experienced as a result of the encounter with the colonisers. The nature of this encounter resulted in the debasement, neglect, and marginalisation of African philosophical positions. Plunged in this epistemic doubt, uncertainty, and imposed decadence, for centuries, many African philosophers grappling with the question, 'Is there an African philosophy?' The question does two main things: on the one hand, it seeks to validate philosophical positions that are uniquely African, and on another hand, the question searches for prescriptive philosophical paradigms for addressing African problems and analysing issues. Most African philosophical engagements do the former. Shedding new light to the question, I argue that a disposition to African philosophy that stems from a need to validate its existence risks being a mere reaction and/or mimicry, and as such, further perpetrates epistemic violence by removing Africa from its lived realities.